‘Roadblocks, speedbumps and potholes’: an investigation into the working conditions of e-hailing drivers in Cape Town, with reference to the city’s registration system - Ismail, Adiel (My University, 2022)
South Africa has experienced an increase in the demand for e-hailing platforms such as Uber, which has been doing business in the country since 2013, and enables passengers to conveniently commute from one place to another. The rapid adoption of ride-hailing services allows users to easily perform online transactions using their mobile devices and wireless networks. Job seekers are attracted to working for e-hailing platforms, particularly amid the devastating economic fallout of the Covid-19 pandemic. These jobs are in demand, as they do not require special training, there is a potential good return and working hours are flexible. However, e-hailing drivers face several work challenges, ranging from personal safety while on the job to profile blocking and scamming. But perhaps the most crucial challenge for drivers who operate in Cape Town is the municipality’s failure to issue operating licences. This research report equivalent, which investigated the process of obtaining an e-hailing operating licence in Cape Town, is anchored on the hypothesis-based inquiry approach for investigative journalists that was developed by award-winning investigative author and academic, Professor Mark Lee Hunter. This portfolio of work is divided into three sections. The opening is academic in nature and contains: the aims and rationale; the literature review; the elements of planning the investigation, such as a source map to identify potential interviewees; a timeline to chronicle pertinent information. The next section is an investigative story that imitates the style of a publishable journalistic news article that offers context, data, interviews, and human interest, and is enhanced by multi-media features. The final section is a reflective essay that assesses the learning, success and limitations of this research project. This investigative research project amplified - albeit modestly - the largely untold experiences of women e-hailing drivers in Cape Town. It confirmed that Uber and the City of Cape Town inadvertently benefit financially from a backlog in processing e-hailing permits. Furthermore, it revealed that, in 2021 the City of Cape Town issued fines in excess of R13 million to e-hailing drivers for a breach of the operating permit by-laws, while not granting a single e-hailing operating licence since February 2021
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts by coursework and research report in Journalism and Media Studies to the Faculty of Humanities, Wits School of Literature, Language and Media, University of the Witwatersrand, 2022